Telemedicine versus face-to-face evaluation in the delivery of thrombolysis for acute ischaemic stroke: a single centre experience. Issue 1037 (19th January 2012) - Chowdhury, Muhibbur; Birns, Jonathan; Rudd, Anthony; Bhalla, Ajay
Abstract : Background: Telemedicine is increasingly used in the UK to deliver thrombolysis. It is primarily used to enable assessment of people presenting with an acute stroke by a remote specialist in stroke care, and to determine eligibility for thrombolysis with alteplase (recombinant tissue plasminogen activator). This study aims to evaluate the process of acute stroke care, safety and outcome profiles when comparing face-to-face evaluation and telemedicine in the delivery of thrombolysis. Methods: This was a retrospective single centre cohort study, evaluating patients thrombolysed from July 2007 to December 2009 inclusive. All patients were given treatment within a 3-hour window from onset of symptoms. Of the 97 patients thrombolysed, 45 (46%) were evaluated by telemedicine. Process times of the steps taken to deliver thrombolysis for the two groups were compared. The authors include the rates of symptomatic intracranial haemorrhage (SICH). Outcome data include 3-month mortality and functional status. Results: Process times were significantly better in face-to-face: Admission to CT (p=0.001), CT to treatment (p≤0.001) and admission to treatment (p≤0.001). SICH occurred in four patients (7.7%) in the face-to-face group compared with the two patients (4.4%) in the telemedicine group (p=0.7). Favourable outcome: a modified Rankin score of 0–2 was observed in 19 patients (36.5%) in the face-to-face group compared with 19 patients (42%) in the telemedicine group (p=0.9). Conclusions: This analysis shows that the use of telemedicine compared with face-to-face evaluation is feasible in the delivery of thrombolysis during out of hours. There are several areas of our emergency process of hyper-acute stroke care that need improving when using telemedicine.